Measurement of Urokinase-Type Plasminogen Activator (u-PA) with an Enzyme-Linked Immunosorbent Assay (ELISA) Based on Three Murine Monoclonal Antibodies - Darras, V; Thienpont, M; Stump, D C; Collen, D (Thrombosis and Haemostasis, 1986)
An enzyme-linked immunosorbent assay (ELISA) for the measurement of urokinase-type plasminogen activator (u-PA) was developed. Three murine monoclonal antibodies to single chain urokinase-type plasminogen activator (scu-PA) were isolated and shown to react with non-overlapping epitopes in scu-PA. Two of the three antibodies were coated onto microtiter plates and bound u-PA was quantitated with the third antibody conjugated to horseradish peroxidase. The assay was equally sensitive to Mr 54,000 u-PA in the single chain or two-chain form but did not respond to Mr 33,000 urokinase. The lower limit of sensitivity of the assay was 0.1 ng/ml in buffer and 1 ng/ml in plasma. Coefficients of variation of the assay at physiological levels of u-PA were 6.5 percent within assays and 13 percent between assays. The level of u-PA in normal resting plasma was 1.9 ± 0.66 ng/ml (mean ± SD, n = 54). The assay can be performed within one working day and provides an efficient, reproducible, and stable means for the measurement of u-PA in biological fluids. As such it may facilitate physiological and pharmacological studies of urokinase-type plasminogen activators in man.
Keywords: ELISA; Urokinase-type plasminogen activator (u-PA); Monoclonal antibodies; Fibrinolysis